Training immunophenotyping deep learning models with the same-section ground truth cell label derivation method improves virtual staining accuracy - Azam, Abu Bakr; Wee, Felicia; Väyrynen, Juha P.; Yim, Willa Wen-You; Xue, Yue Zhen; Chua, Bok Leong; Lim, Jeffrey Chun Tatt; Somasundaram, Aditya Chidambaram; Tan, Daniel Shao Weng; Takano, Angela; Chow, Chun Yuen; Khor, Li Yan; et al. (Frontiers in Immunology, 2024)
Introduction Deep learning (DL) models predicting biomarker expression in images of hematoxylin and eosin (H&E)-stained tissues can improve access to multi-marker immunophenotyping, crucial for therapeutic monitoring, biomarker discovery, and personalized treatment development. Conventionally, these models are trained on ground truth cell labels derived from IHC-stained tissue sections adjacent to H&E-stained ones, which might be less accurate than labels from the same section. Although many such DL models have been developed, the impact of ground truth cell label derivation methods on their performance has not been studied. Methodology In this study, we assess the impact of cell label derivation on H&E model performance, with CD3+ T-cells in lung cancer tissues as a proof-of-concept. We compare two Pix2Pix generative adversarial network (P2P-GAN)-based virtual staining models: one trained with cell labels obtained from the same tissue section as the H&E-stained section (the ‘same-section’ model) and one trained on cell labels from an adjacent tissue section (the ‘serial-section’ model). Results We show that the same-section model exhibited significantly improved prediction performance compared to the ‘serial-section’ model. Furthermore, the same-section model outperformed the serial-section model in stratifying lung cancer patients within a public lung cancer cohort based on survival outcomes, demonstrating its potential clinical utility. Discussion Collectively, our findings suggest that employing ground truth cell labels obtained through the same-section approach boosts immunophenotyping DL solutions.